2016
DOI: 10.18632/oncotarget.13212
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting tumor necrosis factor-alpha diminishes desmoplasia and inflammation to overcome chemoresistance in pancreatic ductal adenocarcinoma

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the most

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 32 publications
5
59
3
Order By: Relevance
“…Interestingly, overexpression of tubulins has been linked to poor response to microtubule‐targeting anticancer drugs . Moreover, elevated levels of tumor necrosis factor have been previously reported in pDAC but not in controls, and were associated with poor survival . In addition, increased levels of tumor necrosis factor were found in pDAC compared to other pancreatic malignancies including pNET, which is in line with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, overexpression of tubulins has been linked to poor response to microtubule‐targeting anticancer drugs . Moreover, elevated levels of tumor necrosis factor have been previously reported in pDAC but not in controls, and were associated with poor survival . In addition, increased levels of tumor necrosis factor were found in pDAC compared to other pancreatic malignancies including pNET, which is in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we detected ion species that exhibited a similar mass to the molecules reported as basic fibroblast growth factor receptor 1, type I and type II collagen, tubulin beta‐2C chain, and tumor necrosis factor receptor, among others . Interestingly, basic fibroblast growth factor, collagens, tubulins, and tumor necrosis factor have all been reported in association with pDAC. We detected these molecules in higher intensities in pDAC compared to pNET.…”
Section: Discussionsupporting
confidence: 76%
“…Our previous studies have shown that TNF-α and TGF-β cytokines can upregulate ZIP14 levels in muscle cells [21]. These cytokines can be detected in the conditioned media of PDAC cell lines and sera of PDAC patients [9,[28][29][30][31][32]. It remains to be tested in future studies whether blocking TNF-α or TGF-β signaling in muscles can reduce Zip14 expression.…”
Section: Discussionmentioning
confidence: 96%
“…Exactly, in some cases, infiltration of tumors by activated T cells reduces the spread of metastasis. The connection of circulating malignant cells with platelets or macrophages may prevent them from NK cell-mediated killing, thereby overcoming immunosurveillance [31]. Systemic inflammation promotesconnection of circulating malignant cells to hepatic sinusoids, and this process is ruled by neutrophil-dependent upregulation of adhesion molecules.…”
Section: Inflammation and Metastasismentioning
confidence: 99%